Donor management using a specialized donor care facility is associated with higher organ utilization from drug overdose donors. Issue 3 (14th December 2020) - Frye, Christian Corbin; Gauthier, Jason M.; Bery, Amit; Gerull, William D.; Morkan, Deniz B.; Liu, Jingxia; Shea Harrison, M.; Terada, Yuriko; Van Zanden, Judith E.; Marklin, Gary F.; Pasque, Michael K.; Nava, Ruben G.; et al.
Abstract: Drug overdoses have tripled in the United States over the last two decades. With the increasing demand for donor organs, one potential consequence of the opioid epidemic may be an increase in suitable donor organs. Unfortunately, organs from donors dying of drug overdose have poorer utilization rates than other groups of brain‐dead donors, largely due to physician and recipient concerns about viral disease transmission. During the study period of 2011 to 2016, drug overdose donors (DODs) account for an increasingly greater proportion of the national donor pool. We show that a novel model of donor care, known as specialized donor care facility (SDCF), is associated with an increase in organ utilization from DODs compared to the conventional model of hospital‐based donor care. This is likely related to the close relationship of the SDCF with the transplant centers, leading to improved communication and highly efficient donor care.